Entrance facing the Hazareshwar and Mahakal temples - Temples of India Project Team (Jio Institute, 2024)
The Kund is surrounded by a tall enclosure wall, with steps provided on three sides which leads to it. One of the entrances, facing the Hazareshwar and Mahakal temples, is adorned with remnants of the temples.